ANALYSIS OF SENSATIONS AROUND THE TRINITY DOCTRINE IN INDONESIA - Georges Nicolas Djone; Leyna Christin Nainggolan; Wahyu Juli Suryaningsih; Weni Lolinga; Tirza Manaroinsong (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The purpose of writing this article is to examine the controversy over the doctrine of the Trinity Doctrine today, as well as to analyze the relevance of the urgency of liberation theology to this teaching today, using a descriptive qualitative method approach through literature analysis and data collection techniques through Bible sources, various books, and journals, as well as various documents related to the object of research. As a result, there is a massive effort to evoke Sabellianism in terms known as "Oneness Pentecostalism" today, especially in Indonesia. In conclusion, the Call for Liberation Theology and the controversy surrounding the Trinity Doctrine is not a sensation in a massive effort to evoke Sabellianism in terms known as "Oneness Pentecostalism" today, especially in Indonesia, so that the relevance of the urgency of the call for a liberation theology to the term and the Trinity teaching is not clear and has the same basis as in the past, even today it is still not strong because precisely the Trinity is not only a characteristic of Christian belief but also the only way of understanding the Living and perfect God YHWH insofar as He reveals Himself to His people and also in this world.